Lichen diversity as an air quality bioindicator in the Mount Tilu Nature Reserve (MTNR) Bandung - Arie Aryanto; Subekti Nurmawati; Na’ilah I. Alifiyah; Hikmah Zikriyani; Fauzan Hamdani; Filemon M. Sinyo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2026)
MTNR in Pangalengan, West Java, is a conservation area with high biodiversity that is increasingly pressured by tourism and agricultural activities, which may affect air quality. This study aimed to examine the relationship between air quality and lichen diversity as bioindicators of air pollution. A descriptive exploratory method was applied at four site types representing different levels of human activity: forest, roadside, plantation, and tourist areas. The results showed that microclimatic conditions and air quality at all sites were classified as good according to Government Regulation No. 22/2021. However, lichen diversity and thallus composition varied among sites in response to environmental conditions. Crustose lichens dominated roadside and plantation areas with higher environmental stress, while foliose and fruticose lichens were more abundant in forest areas characterized by lower temperatures, higher humidity, and minimal pollution. The presence of sensitive species such as Usnea sp. and Ramalina sp. indicated superior air quality in forest sites. In conclusion, lichen distribution reflects an air quality gradient across the study area, confirming the effectiveness of lichens as reliable bioindicators for ecological monitoring in conservation areas.